2016
DOI: 10.1021/jacs.6b05048
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Quantification of MicroRNA in a Single Cell Using Atomic Force Microscopy

Abstract: MicroRNAs (miRNAs) play critical roles in controlling various cellular processes, and the expression levels of individual miRNAs can be considerably altered in pathological conditions such as cancer. Accurate quantification of miRNA at the single-cell level will lead to a better understanding of miRNA function. Here, we present a direct and sensitive method for miRNA detection using atomic force microscopy (AFM). A hybrid binding domain (HBD)-tethered tip enabled mature miRNAs, but not premature miRNAs, to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…All animal care and use were in accordance with the institutional guidelines of Pohang University of Science and Technology. Neuronal cell cultures and AFM imaging were performed as previously described (32). Statistical analysis was performed using IBM SPSS Version 21.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animal care and use were in accordance with the institutional guidelines of Pohang University of Science and Technology. Neuronal cell cultures and AFM imaging were performed as previously described (32). Statistical analysis was performed using IBM SPSS Version 21.0.…”
Section: Methodsmentioning
confidence: 99%
“…A hybrid binding domain (HBD) binds specifically to RNA/DNA hybrids that do not normally exist in the cytosol (31). We previously took advantage of HBD to detect and quantify miRNAs in single cells (32). Using the HBD with a complementary probe DNA to hybridize with miR-134s as the target, we were able to map individual miR-134s in dendritic shafts and spines at 10-nm resolution (SI Appendix, Fig.…”
mentioning
confidence: 99%
“…For example, multifrequency AFM that can provide more information by measuring several frequencies of cantilever motion such as simultaneous measurement of topography and the viscosity map of virions [ 92 ], cells [ 93 ] and VLPs [ 94 ]. It is also possible to use the AFM as a physical micromanipulator in force nanoindentation studies to map the mechanical properties of viruses in uncoating and capsid interaction studies [ 95 , 96 ] and there exists a modification of force spectroscopy using hybrid binding domain functionalised AFM cantilevers to investigate and quantify the in situ hybridization of miRNA and other nucleic acids in single cells [ 97 ].…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…173 Recently, studies have shown that AFM can even directly probe RNA in a fixed cell with biochemically sensitive tips. 174 For more descriptions about AFM imaging of DNA, readers are referred to the reviews.…”
Section: Nucleusmentioning
confidence: 99%